Characterization of Electricity Generated by Soil in Microbial Fuel Cells and the Isolation of Soil Source Exoelectrogenic Bacteria - Jiang, Yun-Bin; Zhong, Wen-Hui; Han, Cheng; Deng, Huan (Frontiers in Microbiology, 2016)
Soil has been used to generate electrical power in microbial fuel cells (MFCs) and exhibited several potential applications. This study aimed to reveal the effect of soil properties on the generated electricity and the diversity of soil source exoelectrogenic bacteria. Seven soil samples were collected across China and packed into air-cathode MFCs to generate electricity over a 270 d period. The Fe(III)-reducing bacteria in soil were enriched and sequenced by Illumina pyrosequencing. Culturable strains of Fe(III)-reducing bacteria were isolated and identified phylogenetically. Their exoelectrogenic ability was evaluated by polarization measurement. The results showed that soils with higher organic carbon content but lower soil pH generated higher peak voltage and charge. The sequencing of Fe(III)-reducing bacteria showed that Clostridia were dominant in all soil samples. At the family level, Clostridiales Family XI. incertae sedis were dominant in soils with lower organic carbon content but higher pH (>8), while Clostridiaceae, Lachnospiraceae and Planococcaceae were dominant in soils with higher organic carbon content but lower pH. The isolated culturable strains were allied phylogenetically to fifteen different species, of which eleven were Clostridium. The others were Robinsoniella peoriensis, Hydrogenoanaerobacterium saccharovorans, Eubacterium contortum and Oscillibacter ruminantium. The maximum power density generated by the isolates in the MFCs ranged from 16.4 to 28.6 mW m-2. We concluded that soil organic carbon content had the most important effect on power generation and that the Clostridiaceae were the dominant exoelectrogenic bacterial group in soil. This study might lead to the discovery of more soil source exoelectrogenic bacteria species.